Serum Levels of Brain-Derived Neurotrophic Factor and Other Neurotrophins in Elite Athletes: Potential Markers of the Use of Transcranial Direct Current Stimulation in Sport - Donati, Francesco; Sian, Veronica; Biasini, Giorgia Morgan; de la Torre, Xavier; Folchitto, Fabrizia; Botrè, Francesco (Frontiers in Sports and Active Living, 2021)
Transcranial Direct Current Stimulation (tDCS) is a non-invasive brain stimulation that may enhance mental and physical performance in sports, representing a potential new form of doping (“brain doping” or “electromagnetic doping”). This study aims to identify diagnostic biomarkers for detecting the possible abuse of tDCS in sport. Brain-Derived Neurotrophic Factor (BDNF) and other neurotrophins (NT, such as beta NGF) were pre-selected as potential candidates since their serum values have been observed to change following tDCS. Neurotrophins were measured using ELISA assays in the serum of elite athletes classified by gender, age, type of sports practiced, and time of sample collection (“in competition” vs. “out of competition”). Single nucleotide polymorphisms (rs6265, rs11030099, and rs11030100) were genotyped to determine their influence on the analytes' basal levels. Athletes older than 35 presented higher BDNF values than younger individuals. Samples collected “in competition” showed higher BDNF concentrations than those collected “out of competition”. The studied polymorphisms appeared to affect only on proBDNF, not altering BDNF serum concentrations. NT-3 and NT-4 were poorly detectable in serum. Our results suggest that BDNF, proBDNF, and beta-NGF may be used as biomarkers to detect the abuse of tDCS in sport doping. To the best of our knowledge, this is the first study aimed to pre-select serum biomarkers to identify the use of tDCS, and represents the first essential step to develop an indirect strategy for the future detection of “brain doping” in sports.